Strain rate and oxidation effects on crack initiation at 600 and 650 °C in a nickel-based superalloy. (3rd May 2016) - Perrais, M.; Seror, A.; Burteau, A.; Andrieu, E.; Poquillon, D.
Abstract : Nickel-based superalloys are sensitive to an oxidation-assisted intergranular crack (OAIC) growth mechanism. Crack initiation during slow strain rate tensile tests is investigated at 600 and 650 °C, at different strain rates, with or without oxidation on a direct-aged material. A V-shaped sample geometry is used to promote damage initiation for a specific stress triaxiality. The critical mechanical loading paths inducing intergranular crack initiation as well as the effect of oxidation are discussed.